Geoquímica isotópica Sr-Nd-Pb na capa carbonática marinoana de Tangará da Serra - MT. - SOUZA, Nayra Michelly das Chagas (Universidade Federal do Pará, 2024)
In the Neoproterozoic post-glacial scenario, cap carbonates are systematically found over diamictites having been deposited immediately after these glacial sediments. Cap carbonates are wordlwide of great interest as they provide information about paleoenvironmental and paleoclimatic conditions for carbonate precipitation, being able to arrive at the composition of sea water at the time of its deposition, in periods of the ocean great disturbance. On the southern edge of the Amazonian craton, the Mirassol d'Oeste and the Guia formations constitute the Marinoan cap carbonate of the Araras Group. At the Calcário Tangará Quarry (Tangará da Serra – MT), these formations are composed of dolomite deposits from moderately deep platform (Mirassol d'Oeste Formation) covered by limestone and bituminous shales from a CaCO3-saturated deep platform (Guia Formation), which overlay the Puga Formation diamictites. Eleven samples located in the middle and upper part of the profile (from 45m to 65m) were used, with the methodologies of Pb-Pb geochronology by Neptune ICP-MS mass spectrometry, Sr isotopic geochemistry by sequential leaching in a MAT-262 TIMS mass spectrometer, and Sm-Nd isotopic geochemistry by total dissolution of the carbonate phase in a Neptune ICP-MS mass spectrometer. The Pb-Pb geochronological data for the Guia Formation confirmed the Marinoan age for cap carbonate deposition, with 622 ± 30 Ma, which is in agreement with previous works. Regarding the Sr isotopic compositions at the base of such a Formation, these provided an 87Sr/86Sr ratio of 0.7071–0.7073, which are among the lowest values found in the world for the cap marinoan. For the upper portion of the Guia Formation, higher values were found (0.70702 ± 00014 to 0.70769 ± 000012; 2σ), which are in agreement with the base of this Formation and with other surrounding Marinoan cap carbonate around the world. Globally, this abrupt increase in Sr isotopic composition is also observed in the various Marinoan cap carbonate, ranging from 0.7070 to 0.7120. The Nd-TDM model ages ranged between 1.85 and 2.54 Ga, with ԐNd(635Ma) values ranging from -11.1 to -4.7, but without an increasing or decreasing trend. The auxiliary methodologies consisted in the identification of the mineralogical composition, through petrography in the optical microscope for the carbonate phase, X-Ray diffraction for the siliciclastic phase, and the quantification of the siliciclastic material, which confirmed the presence of terrigenous material (quartz, feldspar and mica) in the Guia Formation carbonates in different proportions in the samples (from 5.9% to 19.8%). Some diagenetic aspects were also observed in petrography, such as dolomitization and replacement of aragonite fans by calcite. Variations in the isotopic composition of Sr and Nd may reflect a rapid change in the isotopic composition of seawater, possibly related to continental influx, with the incorporation of such elements during diagenesis. The Nd-TDM model ages of the Guia Formation carbonates are comparable to those of the continental crust found in rocks from the Paleoproterozoic provinces of the Amazonian Craton, which forms the basement of the Araras Group. The negative values of ԐNd(635Ma) probably indicate the presence of Nd from suspended material transported from continental to seawater from which the carbonates precipitated. As for Sr, the random variations of Nd-TDM ages and ԐNd values suggest important and rapid changes in the continental contribution to the post-Marinoan oceans.